Systematic Review: Tele-Nursing a Universal Access to Care for Oncology Patients - Yuli Pilar Osorio-Calle; Katterin Joely Sebastián-Aquino; Mónica Elisa Meneses -La-Riva (STIKes Patria Husada Blitar, 2021)
Telenursing is a way of caring for and educating oncology patients to promote self-care management at home. The objective of the study was to analyze the scientific evidence on telenursing in the care of oncology patients. This was a systematic and descriptive review in Spanish, Portuguese and English which was available in 3 databases: BMC, Pubmed and Scielo. The articles were selected in English, Spanish and Portuguese with data from 2010-2020. It was found that tele-nursing, a new form of access to the care service provided by nursing professionals to patients with oncology treatment, including technological tools allow a direct and timely relationship to respond to the detection of adverse events after chemotherapy, promote self-care and control and monitor the patient's health status at home. Conclusions: There is a need to use tele-nursing as an opportunity to care for the patient at home through virtual means by providing relevant information to promote self-care and quality of life.